How transformational leadership influences museums’ performance: a contextual ambidexterity view - Nunes, F. G.; Fernandes, A.; Martins, L.; Nascimento, G. (Museum Management and Curatorship, 2021)
Although researchers and managers recognise the tensional nature characterising the dynamics of museums and show a major concern with museums’ performance, the lack of studies examining organizational antecedents of performance is potentially limiting the understanding of the process by which top managers promote this key outcome. Drawing on the literature on ambidexterity and transformational leadership, we suggest that the transformational leadership of museums’ top managers facilitates the emergence of contextual ambidexterity which, in turn, influences museums’ performance. Data collected from a sample of 38 museums, including their top managers and 256 employees, support our hypotheses.